Evaluation of Mini-Mental State Examination scores according to different age and education strata, and sex, in a large Brazilian healthy sample - Renata Kochhann (Dementia & Neuropsychologia, 2009)
Until better measures have been accepted for wider use, the Mini-Mental State Examination (MMSE) will continue to be utilized. In this context, knowledge on characteristics and determinants of its distribution for the Brazilian population are particularly valuable. The present study aimed to evaluate, based on multivariate analysis, the independent effect of age, educational level and sex, and their interactions, on MMSE scores in a healthy sample. Methods: Demographic data and scores on the MMSE of 1,553 healthy individuals were analyzed. The sample was grouped according to age and education. Results: The sample was composed of 963 females (62%), mean age ±SD was 49.6±20.7 yrs (range 20 to 92 yrs). The mean years of education ±SD was 8.9±5.5 yrs (range 0 to 28 yrs). The mean score ±SD on the MMSE was 27.3±2.7 (range 15 to 30). A significant effect of the interaction between education and sex (p=0.011), and also between education and age was observed (p=0.003). An independent effect of education (p<0.001) and age (p<0.001) was found. Participants from the higher educated group presented higher MMSE scores than the other groups. Younger adults presented higher MMSE scores than the other age groups. Conclusions: We observed an effect of education and age on MMSE scores. Younger individuals and higher educated participants presented higher scores.